2017
DOI: 10.22202/tus.2017.v3i1.2520
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of English Song in Building English Vocabulary at Murni Kindergarten Padang

Abstract: Penelitian ini bertujuan untuk menganalisis penerapan lagu Bahasa Inggris dalam memperkenalkan kosakata Bahasa Inggris oleh guru di Taman Kanak–Kanak Murni Padang. Peneliti menganalisis tahap penerapan sebuah lagu bahasa Inggris yang dapat digunakan oleh guru Bahasa Inggris dalam memperkenalkan kosakata Bahasa Inggris berdasarkan teori dari Case, Lynch, dan Sophya. Penelitian ini merupakan penelitian deskriptif. Dalam penelitian ini, peneliti meminta peneliti sejawat memberikan evaluasi dalam bentuk ceklis obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Finally, the teacher and the students sang a song together. This is consistent with previous research by [21] and [22], who stated that because the song is used to create a comfortable and fun learning environment, the end of the implementation song must be memorable by inviting students to sing the song together so that they feel that the learning activity is meaningful.…”
Section: Implementing Of Song In Learning Englishsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, the teacher and the students sang a song together. This is consistent with previous research by [21] and [22], who stated that because the song is used to create a comfortable and fun learning environment, the end of the implementation song must be memorable by inviting students to sing the song together so that they feel that the learning activity is meaningful.…”
Section: Implementing Of Song In Learning Englishsupporting
confidence: 91%
“…In the post-activity, the teacher concludes the class by singing with the students to maintain the atmosphere of the class that has already been adapted to the activity with song and to make a good last impression for the student so students are motivated to learn again even though the teacher did not sing a song for a long time in the post activity due to the location in the countryside, which makes it difficult for teachers to even rarely use the YouTube video Furthermore, some students' lack of response makes it difficult for the teacher to invite students to close the lesson by singing together before the class ends. Based on this explanation, it can be seen that the teacher wanted to create an interesting closing as stated by [21] and [22], in which the song is used to make a comfortable and fun learning climate, the ending of implementing song must be memorable by inviting students to sing the song together so that they feel that the learning activity is meaningful.…”
Section: Implementing Of Song In Learning Englishmentioning
confidence: 99%
“…When teaching English vocabulary using songs, students become more motivated so that students more easily remember and memorize new vocabulary so that students' vocabulary increases. The results of this study are the same as those of the researchers Mokhtar et al (2017) said that the use of English songs in construction. The teacher implemented Murni kindergarten students' vocabulary, and the student's English vocabulary building progressed step by step.…”
Section: How Songs Can Encourage Aisyiyah Bustanul Athfal (Aba) 51 Ki...supporting
confidence: 86%
“…Songs can be used as a medium to help students improve their pronunciation, vocabulary, and fluency. The song's words and rhyme are exciting and enjoyable for students because many things can be taught to Kindergarten students through songs that will stay with them throughout their lives (Mokhtar et al, 2017). The use of song will allow students to develop themselves and their feelings, and it can also help students make sense of and solve problems, as mentioned by Parlakian (cited in Hadi, 2019).…”
Section: A Introductionmentioning
confidence: 99%
“…Next, the results of research showed that English song benefits teaching and learning English vocabulary to Kindergarten pupils. It can be seen from an observation about the implementation of English songs in building Murni Kindergarten pupils' vocabulary implemented by the teacher, and the pupils' English vocabulary building increased step by step (Džanić & Pejić, 2016;Mokhtar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%